Engineered human B cells targeting tumor-associated antigens exhibit antigen presentation and antibody-mediated functions - Boucher, Alexander; Anderson, Courtney; Hinman, Rochelle; Kindschuh, Molly; Fung, Jeremy; Wang, Tiansu; Klooster, Isabella; Kim, Elise; Roth, Caroline; Vander Oever, Michael; Khan, Bakhmala; Zelikson, Natalie; et al. (Frontiers in Immunology, 2025)
B cell engineering represents a promising therapeutic strategy that recapitulates adaptive immune functions, such as memory retention, antibody secretion and affinity maturation in murine models of viral infection. These mechanisms may be equally beneficial in oncology. Recent studies have linked endogenous anti-tumor B cell immunity to favorable prognosis across multiple malignancies. Here, we present functional validation of human B cells engineered to target tumor-associated membrane and intracellular antigens. We demonstrate that engineered B cells express therapeutically relevant membrane B cell receptors that are secreted as antibodies upon differentiation. Additionally, engineered B cells take up tumor-associated antigens and demonstrate potent antigen presentation capabilities, while their secreted antibodies activate T cell responses via immune complexes and induce tumor-directed cytotoxic responses. B cell engineering to target tumor-associated antigens may thus have utility as a novel modality for solid tumor therapy.